Host defences to Citrobacter rodentium - Simmons, Cameron (2018)
Citrobacter rodentium is a natural non-invasive bacterial pathogen which infects the distal colon of mice. It uses the same molecular mechanisms of type III secretion as human enteropathogenic and enterohemorrhagic Escherichia coli to colonise the epithelial cells of the gut and is therefore an ideal model to study host-bacterial pathogen interactions in vivo. Infection elicits mucosal inflammation with similarities to inflammatory bowel disease, and so it is a readily accessible model to investigate the relationship between inflammation and anti-bacterial immunity in the gut.